Dietary supplementation in competitive swimming: Analysis of prevalence and gender-differences - Liposek, S. (SportMont, 2024)
Dietary supplementation (DS) is an important factor in contemporary sports, but studies rarely have examined DS practices in high-level swimming. The aim of this study was to investigate the practice of DS in professional swimming, emphasizing the differences between male and female swimmers. The participants were 301 swimmers from Slovenia (148 females; 16.7±2.1 years of age; 9.2±3.1 years of experience in swimming sports), comprising the population of swimmers from Slovenia who competed at the highest level of national competition. Variables were collected via a previously validated questionnaire tool and included DS factors (i.e., knowledge of DS, boundaries, sources of information) and specific usages of the different supplements. The chi-square test and Mann-Whitney test (MW) were used to evaluate differences between genders. Only 30% of the studied swimmers reported not using the DS. Isotonics and vitamins/minerals are mostly used (19% and 18% of regular users, respectively). Males use DS more often than females do (MW=2.90, p=0.03), with a higher consumption of carbohydrates and amino acids in males (MW=2.53 and 2.14, respectively, p